EARLY MEDIA VIEWING IMPACTS ON DUAL LANGUAGES ACQUISITION OF A YOUNG LEARNER - Sudarsono, Sudarsono (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2019)
Despite all benefits of technology, a young child who is exposed to two languages through early media viewing may experience language development problems. It may consequently lead one to undergo therapies which can be counterproductive to their developmental milestones, especially to their dual language development. This research aims to gain deeper insights into the impacts of early media viewing on a young child's early dual language acquisition. A case study of a young dual language learner experiencing language development problems diagnosed as symptoms of Autistic Spectrum Disorder (ASD) was conducted by interviewing participant’s parents to gain preliminary data about his language development problems. Observations took place during 108-hour language intervention sessions. The finding shows that early dual language exposure through early media viewing without adequate social interaction with peers and adults pertinently results in language development problems which are prone to be interpreted as symptoms of ASD rather than as a natural process of bilingualism.